Midgut microbiota affects the intestinal barrier by producing short-chain fatty acids in Apostichopus japonicus - Song, Mingshan; Zhang, Zhen; Li, Yanan; Xiang, Yangxi; Li, Chenghua (Frontiers in Microbiology, 2023)
The intestinal microbiota participates in host physiology and pathology through metabolites, in which short chain fatty acids (SCFAs) are considered as principal products and have extensive influence on intestine homeostasis. It has been reported that skin ulceration syndrome (SUS), the disease of Apostichopus japonicus caused by Vibrio splendidus, is associated with the alteration of intestinal microbiota composition. To investigate whether the intestinal microbiota affects A. japonicus health via SCFAs, here, we foucus on the SCFAs profiling and intestinal barrier function in A. japonicus by treated with V. splendidus. Firstly, we found that V. splendidus could destruct mid-intestine integrity and downregulate the expression of tight junction proteins ZO-1 and occludin in A. japonicus, which further dramatically decrease microorganism abundance and alter SCFAs contents. Especially, acetic acid is associated with the greatest number microorganisms and has significant correlation with occludin and ZO-1 among the seven SCFAs. Furthermore, our findings showed that acetic acid could maintain intestinal barrier function via increasing the expression of tight junction proteins and rearrangement of tight junction structure through regulating F-actin in mid-intestine epitheial cells. Thus, our results provide insights into the impact of gut microbiome and SCFAs on intestine barrier homeostasis and provide essential knowledge for intervening in SUS by targeting the metabolites or gut microbiota.